Plasma Chemerin Levels Are Increased in ST Elevation Myocardial Infarction Patients with High Thrombus Burden - Ahmet Hakan Ateş; Uğur Arslan; Aytekin Aksakal; Ahmet Yanık; Metin Özdemir; Selim Kul (Cardiology Research and Practice)
Objective. To investigate plasma chemerin levels in ST elevation myocardial infarction (STEMI) patients and find out possible relationships between plasma chemerin levels and angiographic characteristics. Patients and Methods. Ninety-seven consecutive patients who presented with STEMI and underwent primary percutaneous coronary intervention (PCI) with coronary stents were enrolled, and 30 age- and sex-matched patients with stable angina pectoris who underwent coronary angiography formed the control group. Angiographic characteristics of the patients including thrombolysis in myocardial infarction (TIMI) thrombus and Gensini scores were noted. Blood samples were taken to detect several biochemical markers including plasma chemerin levels at the admission to hospital. Results. Serum chemerin and C-reactive protein (CRP) levels were significantly increased in patients with STEMI. Among STEMI patients, serum chemerin levels were significantly higher in patients with high thrombus burden (581.5 ± 173.7 versus 451.3 ± 101.2 mg/dL, p<0.001). CRP levels and peak creatine kinase-MB (CK-MB) levels were higher, and left ventricular ejection fraction and post-PCI TIMI flow were lower in patients with high thrombus burden. After multivariate analysis, serum chemerin levels were also higher in patients with high thrombus grade (odds ratio: 1.009 (1.005–1.014), p<0.001). Besides, serum chemerin levels were also found to be significantly correlated with CRP r=0.47,p<0.001 and peak CK-MB r=0.376,p<0.001 levels. Conclusions. Results from our study have demonstrated for the first time that chemerin levels were higher in STEMI patients with greater thrombus burden and higher level of inflammation.